SIU-ICUD on bladder cancer: pathology - Compérat, Eva; Babjuk, Marek; Algaba, Ferran; Amin, Mahul; Brimo, Fadi; Grignon, David; Hansel, Donna; Hes, Ondra; Malavaud, Bernard; Reuter, Victor; van der Kwast, Theo (World journal of urology, 2019)
Many changes have been made during these last years and concepts for understanding bladder cancer have evolved. We make an update with the latest findings of the WHO (World Health Organistaion) 2016, ICCR (International Collaboration on Cancer Reporting) and other official organisms and try to show the latest developments. In this document we provide new consensus guidelines and insights. We kept this document short and concise providing consensus guidelines to clinicians for the best patient care, it should be easy to understand for a non pathologists. We focussed on several burning issues, such as the anatomical and histological understanding of the bladder wall, the prognostic significance of grading and the most challenging problems in staging, we underline our needs from the clinicians such as clinical information, we further discuss the histological subtypes of bladder cancer, which is an extremely important issue in the light of molecular classifications and give prognostic insights. Furthermore, we discuss the ICCR worldwide consensus reporting, urinary cytology with the Paris system and several issues such as frozen section specimen.
Keywords: stupeň nádoru; směrnice pro lékařskou praxi jako téma; Neoplasm Staging; Societies, Medical; staging nádorů; Urinary Bladder Neoplasms; Practice Guidelines as Topic; Grade; Histology; Pathology; Humans; společnosti lékařské; Consensus; nádory močového měchýře; Stage; lidé; konsensus; Neoplasm Grading